2019
DOI: 10.1128/aac.01006-18
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Saksenaea sp. Osteomyelitis by Conservative Surgery and Intradiaphyseal Incorporation of Amphotericin B Cement Beads

Abstract: Osteoarticular mucormycosis cases are quite rare and challenging infections that are mostly due to direct inoculation during traumatic injury among immunocompetent patients. Classic management includes a combination of aggressive surgical debridement, which may lead to amputation, and long-term systemic liposomal amphotericin B therapy. This article describes the successful treatment of Saksenaea sp. osteomyelitis in a patient with diabetes mellitus, using a combination of systemic antifungal therapy and conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is interesting to note that amphotericin B, a drug that is being the first choice for treatment of mucormycoses (2) including those caused by the Saksenaea species (e.g. (69), showed only very weak activity against S. dorisiae . From the azoles used in the study, ketoconazole, posaconazole and itraconazole showed weak activity at rather high minimum effective concentrations, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that amphotericin B, a drug that is being the first choice for treatment of mucormycoses (2) including those caused by the Saksenaea species (e.g. (69), showed only very weak activity against S. dorisiae . From the azoles used in the study, ketoconazole, posaconazole and itraconazole showed weak activity at rather high minimum effective concentrations, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…New topical formulations, like aerosolized L-AmB, show promise for local intrapulmonary drug delivery, decreasing systemic absorption and improving survival when administered early. There are anecdotal reports on the use of AmB eye drops for keratitis, oral AmB for gastrointestinal mucormycosis, intradiaphyseal incorporation cement beads in osteomyelitis, intrathecal administration in cerebral abscess, and percutaneous injection in cutaneous lesions [7,[70][71][72][73][74]. The optimal usage of these formulations in conjunction with systemic therapy is yet to be determined [7].…”
Section: Management Of Mucormycosismentioning
confidence: 99%
“…Furthermore, rhino-orbito-cerebral and disseminated infections have been reported [1, 2]. Classic management of the infection site usually includes a combination of broad, aggressive and repeated surgical debridement (which may lead to amputation), and long-term systemic therapy with appropriate antifungals, preferably liposomal amphotericin B and/or posaconazole [69]. Antifungal therapy alone seems to be inadequate to control infection [2].…”
Section: Introductionmentioning
confidence: 99%